Effekter av bearbetningsdjup i plöjningsfri odling - Sörensson, Fredrik (SLU/Dept. of Soil and Environment, 2015)
In Sweden, reduced tillage usually means non-inversion tillage, where primary tillage is carried out using chisel ploughs or disc implements. Primary tillage method is mainly determined by the desired soil loosening and the handling of soil residues.